2020
DOI: 10.1021/acsnano.0c01298
|View full text |Cite
|
Sign up to set email alerts
|

Massive Growth of Graphene Quartz Fiber as a Multifunctional Electrode

Abstract: Quartz fiber, a widely used reinforcer with high tensile strength and excellent heat resistance, can have more attractive electrical applications such as electromagnetic interference shielding, static dissipation, and strain sensing if it becomes conductive. Many attempts have been made to increase the electrical conductivity of quartz fiber by surface coating of conductive polymers or plating of metal films, but suffers from sacrificing flexibility and causing heavy metal pollution. Here we designed and massi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…Furthermore, we demonstrated that the bandgap of the GO sheets was reduced by rolling them into tubes. Unlike the 2D structures of graphene formed on a solid surface, [23][24][25] 2D manifolds of GO in a fluid medium have a large surface area. They have the advantage of a millimeter-scale persistence length and elasticity compared to a single-layer GO sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we demonstrated that the bandgap of the GO sheets was reduced by rolling them into tubes. Unlike the 2D structures of graphene formed on a solid surface, [23][24][25] 2D manifolds of GO in a fluid medium have a large surface area. They have the advantage of a millimeter-scale persistence length and elasticity compared to a single-layer GO sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene quartz fibre (GQF) are suitable for industrial electronic heaters and real-time biomimetic gas sensor [ 234 , 235 ]. Gas sensors are used to screen the air quality, environment, and to sense the presence of different toxic gases such as carbon dioxide, methanol, ethanol, ethylene, formaldehyde, and acetone [ 236 ].…”
Section: Applications Of Graphene-based Materialsmentioning
confidence: 99%
“…The preparation process of a graphene-based gas sensor is easier and more cost-effective than the other metal-based sensors, which eventually increase its applications in diversified areas [ 236 , 237 ]. They can be knitted into meter-scaled knit fabrics with excellent electrothermal conversion efficiency, high sensitivity, fast response (<0.5 s), and good durability (~5000 cycles) to organic solvent vapour [ 234 ]. As shown in Figure 13 , graphene/polymer composites are used in different sensor elements, especially for healthcare [ 238 ] and environmental control systems [ 239 ].…”
Section: Applications Of Graphene-based Materialsmentioning
confidence: 99%
“…Herein, by virtue of our graphene growth experience on SiO 2 fiber by CVD method, [ 26 , 27 , 28 ] a flexible papyraceous freestanding graphene fabric film (FS‐GFF) was designed. In case of using nickel/copper fiber as growth substrate, the large diameter (≈100µm) of metal fiber and the loose structure of common metal mesh may cause a degradation of its original fabric structure and make it unable to be freestanding.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] But the tight integration between graphene film and substrate limits further structure design, while the inevitable tedious transfer process could also cause defects and degrade the properties of graphene. [20][21][22][23][24][25] Herein, by virtue of our graphene growth experience on SiO 2 fiber by CVD method, [26][27][28] a flexible papyraceous freestanding graphene fabric film (FS-GFF) was designed. In case of using nickel/copper fiber as growth substrate, the large diameter (≈100μm) of metal fiber and the loose structure of common metal mesh may cause a degradation of its original fabric structure and make it unable to be freestanding.…”
Section: Introductionmentioning
confidence: 99%